ESPECTRO ENDOR DE ^155Gd^3+: ThO_2 - Fainstein, Carlos (Comisión Nacional de Energía Atómica. Instituto Balseiro, 1973)
Fil. Fainstein, Carlos. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina